Effects of BPD tendencies and subjective well-being on NSSI in adolescents with PTSD - Deng, Weixi; Yan, Shu; Xu, Yongjun; Lu, Zhaoyuan; Liu, Lianzhong; Zhou, Yang; Chen, Mo (Frontiers in Psychiatry, 2023)
Background: Severe posttraumatic stress disorder (PTSD) may lead to nonsuicidal self-injury (NSSI), and borderline personality disorder (BPD) tendencies may play a role in this process. Secondary vocational students experience more social, familial and other pressures and are more vulnerable to psychological problems. Thus, we explored the effect of BPD tendencies and subjective well-being (SWB) on NSSI in secondary vocational students with PTSD. Methods: A total of 2,160 Chinese secondary vocational students in Wuhan participated in our cross-sectional investigation. The Diagnostic and Statistical Manual of Mental Disorders, 5th edition (DSM-5), criteria for PTSD, NSSI Questionnaire, Personality Diagnostic Questionnaire-4+, Subjective Well-Being Scale, and Family Adaptation, Partnership, Growth, Affection, and Resolve (APGAR) Index were used. We conducted a binary logistic regression model and linear regression analysis. Results: Sex (odds ratio [OR]=0.354, 95% confidence interval [CI]=0.171-0.733), BPD tendencies (OR=1.192, 95% CI=1.066-1.333) and SWB (OR=0.652, 95% CI=0.516-0.824) were independent factors that predicted NSSI in secondary vocational students with PTSD. Spearman’s correlation analysis showed that BPD tendencies were positively correlated with NSSI frequency (r=0.282, P<0.01). SWB was negatively correlated with NSSI frequency (r=-0.301, P<0.01). The linear regression showed that BPD tendencies (β=0.137, P<0.05 and β=-0.230, P<0.001) were significantly correlated with NSSI frequency. Spearman’s correlation analysis showed that family functioning was positively correlated with SWB (r=0.486, P<0.01) and negatively correlated with BPD tendencies (r=-0.296, P<0.01). Conclusions: In adolescents, PTSD in response to stressful events could lead to NSSI, and BPD tendencies promote the intensity of NSSI, while SWB diminishes its intensity. Improvement in family functioning may actively guide the development of mental health and improve SWB; such steps may constitute interventions to prevent or treat NSSI. Keywords: posttraumatic stress disorder, nonsuicidal self-injury, personality characteristics, subjective happiness, adolescent